2015
DOI: 10.1080/10826076.2015.1091978
|View full text |Cite
|
Sign up to set email alerts
|

No Quantifiable Carbonyls, Including Formaldehyde, Detected in Voke® Inhaler

Abstract: Introduction: Carbonyls such as formaldehyde, acetaldehyde and acrolein have been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…E-cigarette use is regarded by many (but not all) scientists as being likely to have substantially lower levels of risk than smoking tobacco cigarettes. , Support for this position comes from in vitro biological studies , and the relatively simple composition of e-cigarette aerosols in comparison to cigarette smoke with its thousands of constituents . A growing number of studies have also investigated the emissions of some cigarette smoke toxicants from e-cigarettes, such as tobacco-specific nitrosamines, tobacco alkaloids and nicotine decomposition products, ,, volatile organic compounds, ,, aromatic amines, CO, polycyclic aromatic hydrocarbons (PAHs), ,, phenolics, , metals, ,,, and carbonyls. ,,, Most of these studies report aerosol emission levels of toxicants that are either undetectable or a few percent of those found in cigarette smoke, and comparisons have also been made to room air . However, the presence of toxicants in e-cigarette aerosols, even at comparatively low levels, suggests that e-cigarette use is not risk-free.…”
Section: Introductionmentioning
confidence: 99%
“…E-cigarette use is regarded by many (but not all) scientists as being likely to have substantially lower levels of risk than smoking tobacco cigarettes. , Support for this position comes from in vitro biological studies , and the relatively simple composition of e-cigarette aerosols in comparison to cigarette smoke with its thousands of constituents . A growing number of studies have also investigated the emissions of some cigarette smoke toxicants from e-cigarettes, such as tobacco-specific nitrosamines, tobacco alkaloids and nicotine decomposition products, ,, volatile organic compounds, ,, aromatic amines, CO, polycyclic aromatic hydrocarbons (PAHs), ,, phenolics, , metals, ,,, and carbonyls. ,,, Most of these studies report aerosol emission levels of toxicants that are either undetectable or a few percent of those found in cigarette smoke, and comparisons have also been made to room air . However, the presence of toxicants in e-cigarette aerosols, even at comparatively low levels, suggests that e-cigarette use is not risk-free.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have demonstrated that thermal degradation of PG and GLY can occur to produce compounds such as carbonyls (e.g., formaldehyde, acetaldehyde, and acrolein) that can be detected in EVP aerosols at levels higher than those found in the corresponding e-liquid. , They have also demonstrated that formation of these compounds is correlated to the temperature of the electrical heating element found in EVPs during aerosol formation. , Data (unpublished) indicated it was possible that α-dicarbonyl compounds could form under certain thermal conditions experienced during EVP aerosol formation. Measurable levels of DA and AP in EVP liquids and aerosols were also reported by Allen et al and Moldoveanu et al Consequently, the primary objective of this work was to confirm the formation of α-dicarbonyls during the thermal process of EVP aerosol formation and investigate the mechanism of their formation.…”
Section: Introductionmentioning
confidence: 99%